DNA Engineering and Hepatitis B Virus Replication - Chun-yang Gan (Frontiers Media S.A., 2021)
Recombinant DNA technology is a vital method in human hepatitis B virus (HBV), producing reporter viruses or vectors for gene transferring. Researchers have engineered several genes into the HBV genome for different purposes; however, a systematic analysis of recombinant strategy is lacking. Here, using a 500-bp deletion strategy, we scanned the HBV genome and identified two regions, region I (from nt 2,118 to 2,814) and region II (from nt 99 to 1,198), suitable for engineering. Ten exogenous genes, including puromycin N-acetyl transferase gene (Pac), blasticidin S deaminase gene (BSD), Neomycin-resistance gene (Neo), Gaussia luciferase (Gluc), NanoLuc (Nluc), copGFP, mCherry, UnaG, eGFP, and tTA1, were inserted into these two regions and fused into the open reading frames of hepatitis B core protein (HBC) and hepatitis B surface protein (HBS) via T2A peptide. Recombination of 9 of the 10 genes at region 99–1198 and 5 of the 10 genes at region 2118–2814 supported the formation of relaxed circular (RC) DNA. HBV DNA and HBV RNA assays implied that exogenous genes potentially abrogate RC DNA by inducing the formation of adverse secondary structures. This hypothesis was supported because sequence optimization of the UnaG gene based on HBC sequence rescued RC DNA formation. Findings from this study provide an informative basis and a valuable method for further constructing and optimizing recombinant HBV and imply that DNA sequence might be intrinsically a potential source of selective pressure in the evolution of HBV.